MANAGEMENT OF VILLAGE FUNDS IN LOK SUGA VILLAGE, HAUR GADING DISTRICT, NORTH HULU SUNGAI REGENCY - Anna Maryati; Norhidayah Norhidayah; Nasripani Nasripani (International Journal of Economic Integration and Regional Competitiveness, 2024)
Objective: This study aims to determine the Management of Village Funds in Lok Suga Village, Haur Gading District, Hulu Sungai Utara Regency and determine the factors that influence it. Method: This research uses a qualitative approach with a descriptive-qualitative research type. Data collection techniques used are interviews, observation, and documentation. Data sources were taken using the snowball sampling technique, totaling 16 people. After the data is collected, it is then analyzed using techniques including data reduction, data presentation and conclusion. Tests for the credibility of the data used are extended observations, triangulation, analysis of negative cases, use of references, and member checks. Results: The results of the study show that village fund management in Lok Suga village, Haur Gading district, Hulu Sungai Utara district is good in terms of strategy for achieving goals, activity plans, implementing research activities, recording expenses, and preparing reports. As for the aspects that have not gone well, namely recording income, submitting reports, monitoring the preparation of the budget, and monitoring the utilization of the budget. Furthermore, the factors that influence the management of village funds in Lok Suga village for the inhibiting factors are budget plans that are not in accordance with the budget, and there is no supervision from the BPD. And for the supporting factors, namely the preparation of good reports and effective action plans. Novelty:The novelty of this study lies in its comprehensive qualitative evaluation of village fund management by simultaneously examining planning, implementation, administration, reporting, accountability, and supervision, while explicitly identifying both inhibiting and supporting factors at the village governance level, particularly the absence of BPD supervision and the non-existence of BUMDes as structural constraints in village financial management.